Does catheter ablation of atrial fibrillation eliminate the need for anticoagulation?. (April 2013) - Mahajan, Rajiv; Pathak, Rajeev; Lim, Han S; Willoughby, Scott R; Sanders, Prashanthan
The data from observational studies provide evidence that successful ablation may modify the natural progression of atrial fibrillation. The alteration in risk of stroke may have an influence on the decision to start anticoagulation, which, in turn, exposes the patient to an increased risk of bleeding. However, the definition of 'successful ablation' is arbitrary, and success rates are affected by the intensity of monitoring after the ablation. The duration of an atrial fibrillation episode that elevates the risk of thromboembolism has been reported to be <6 min to 24 h. Furthermore, it is not clear whether there is an increased risk of cardioembolic stroke risk in patients with high CHADS2 scores in sinus rhythm. The data from observational studies are persuasive enough to justify a randomized trial to conclusively answer this question.